The labour market impact of international trade: Methodological approaches for macro- and mesolevel assessments - Monica Hernandez (International Labour Organization (ILO), 2020)
This working paper examines methodological approaches for the empirical assessment of the labour market impact of international trade at the macro and meso level. It considers the underlying assumptions, data requirements and the advantages and limitations associated with each of these approaches in order to evaluate their adequacy and to inform policymaking. A major takeaway of this review is that the approaches commonly used for such assessments tend to focus on quantitative changes in the level of employment and wages, while paying less attention to other aspects related to working conditions. This paper argues that a methodological approach based on mixed methods and drawing on a broader set of indicators can provide more comprehensive insights into the impact of international trade on labour markets.
Keywords: 330; working conditions; globalization; trade; developed countries; developing countries